2001
DOI: 10.1152/jn.2001.86.5.2559
|View full text |Cite
|
Sign up to set email alerts
|

Neural Representation of the Luminance and Brightness of a Uniform Surface in the Macaque Primary Visual Cortex

Abstract: The perceived brightness of a surface is determined not only by the luminance of the surface (local information), but also by the luminance of its surround (global information). To better understand the neural representation of surface brightness, we investigated the effects of local and global luminance on the activity of neurons in the primary visual cortex (V1) of awake macaque monkeys. Single- and multiple-unit recordings were made from V1 while the monkeys were performing a visual fixation task. The class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
155
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(170 citation statements)
references
References 32 publications
12
155
3
Order By: Relevance
“…The perceived brightness of a surface depends not only on surface luminance but also on the luminance distribution in the surrounding visual field (26, ʈ). It has already been demonstrated in cats and monkeys that single neurons in primary visual cortex exhibit a surround modulation that matches contextual effects in human brightness perception (6,9,27,28). By establishing the dynamics of surface-related responses in early visual cortex, our findings therefore provide the fundamental information necessary for the interpretation of future neuroimaging studies of contextual effects in human subjects.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The perceived brightness of a surface depends not only on surface luminance but also on the luminance distribution in the surrounding visual field (26, ʈ). It has already been demonstrated in cats and monkeys that single neurons in primary visual cortex exhibit a surround modulation that matches contextual effects in human brightness perception (6,9,27,28). By establishing the dynamics of surface-related responses in early visual cortex, our findings therefore provide the fundamental information necessary for the interpretation of future neuroimaging studies of contextual effects in human subjects.…”
Section: Discussionsupporting
confidence: 66%
“…Theoretical accounts of surface perception have therefore often postulated a processing of ''filling in'' that mediates creation of surface representations at some level in the visual system (4,5). However, more recent reports suggest that some cells in primary visual cortex do indeed respond to the luminance of uniform surfaces (6)(7)(8)(9)(10). Furthermore, in humans there is a close relationship between perceived brightness contrast and responses in primary visual cortex (11)(12)(13)(14)(15), suggesting that other sensations of brightness may also be encoded in primary visual cortex.…”
mentioning
confidence: 99%
“…The activity of these brightness-responsive neurons adapts with time: the firing rates peak after 100 ms and then drop off precipitously14. This decrease in firing is consistent with an adapting population, although in some circumstances the later part of the spike train may correspond to the response of a non-adapting population 14 . This raises the possibility that the two encodings could be multiplexed into the same population of cells in V1.…”
supporting
confidence: 68%
“…We found that the MEG response was better accounted for by log-scaled luminance (Table 1, middle) than was the physical luminance of the stimulus (Table 1, left). Some electrophysiological studies with non-human primates reported that the electrical activity of neurons in the primary visual cortex depends linearly on the logarithm of luminance (Kayama et al, 1979;Kinoshita & Komatsu, 2001). There are also a few fMRI and EEG studies of humans, which suggest that the activation intensity in the primary visual cortex is linearly dependent on the logarithm of luminance contrast (Avidan, Harel, Hendler, Ben-Bashat, Zohary, & Malach, 2002;Boynton, Demb, Glover, & Heeger, 1999;Goodyear & Menon, 1998;Souza, Gomes, Saito, Filho, & Silveira, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A few electrophysiological studies with non-human primates have reported that individual Correspondence concerning this article should be addressed to Aki Kondo, Research Center for Advanced Science and Technology, The University of Tokyo, 4-6-1, Komaba, Meguro-ku, Tokyo, 1538904, Japan, (email: kondo@fennel.rcast.u-tokyo.ac.jp). neurons exhibit a compressive dependency of discharge rate on luminance, and that neural activity depends linearly on the logarithm of luminance in the primary visual cortex (Kayama, Riso, Bartlett, & Doty, 1979;Kinoshita & Komatsu, 2001).…”
mentioning
confidence: 99%